Mistik Grafika - Widyatmoko, FX (AKSA: Jurnal Desain Komunikasi Visual, 2024)
This article wants to answer curiosity. The author's curiosity is about things that are common or commonplace in everyday life, but maybe (the author) doesn't pay enough attention to them. Why are bibles printed and bound in thick volume? That's the question of curiosity. Even though it tries to answer the curiosity about why the bible is bound in thick binding, this article does not choose to answer it through history. This article chooses to reflect this curiosity. One way the author chose is through graphics. Coincidentally, history and graphic design are close to graphics. Whether or not there is a relationship between graphic design, scripture and graphics, this article also aims to answer this in the form of reflection. At least the presence of design in graphics is not limited to the technical area but also touches the philosophical (aesthetic) area. In order to answer this curiosity, this article will take a soliloquy in three sessions. The first session, about graphics. The second session was about graphic mystical and in this session the design of the bible began to be discussed. This second session consists of two parts. The final session, conclusion, is about how graphics and graphic design learn from history.